2013
DOI: 10.1074/jbc.m113.482596
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Human IκB Kinase β Asymmetric Dimer

Abstract: Background: IB kinase ␤ is a key regulator in the NB signaling pathway. Results: Crystal structure of a human IKK␤ asymmetric dimer shows one kinase active site phosphorylated and in the active conformation and the other unphosphorylated and inactive. Conclusion: Depending on the phosphorylation state, IKK␤ can adopt distinct dimeric geometry. Significance: High resolution structure of hIKK␤ provides structural basis for its activation and potential use of inhibitor design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
141
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(147 citation statements)
references
References 46 publications
1
141
1
Order By: Relevance
“…30 A comparison of other species shows this region to be highly conserved among IKKb orthologs (Table 2A). Even more surprising is the very strict conservation of this region, including the Lys corresponding to Lys147 of IKKb, in a very large number of human kinase paralogs (Table 2B).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…30 A comparison of other species shows this region to be highly conserved among IKKb orthologs (Table 2A). Even more surprising is the very strict conservation of this region, including the Lys corresponding to Lys147 of IKKb, in a very large number of human kinase paralogs (Table 2B).…”
Section: Discussionmentioning
confidence: 98%
“…We demonstrate that the mutation K171E leads to constitutive activation of the intrinsic kinase activity of IKKb, suggesting a role of the normal Lys171 side chain in stabilizing an inactive kinase in addition to its www.landesbioscience.comdocumented importance in the activated structure. 30 Other mutations at this position also result in constitutive activation of IKKb, demonstrated by in vitro kinase assay and phosphorylation of the activation loop residues S177/S181. Such mutations also result in significant activation of STAT3 signaling, which is independent of TNFa or IL-6 stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysine 171 of IKK␤ is a residue that is located parallel to the phosphorylation site in the activation loop. Examination of the structure of phosphorylated versus non-phosphorylated (27) IKK␤ revealed that this residue is part of a cationic pocket, also made up of Arg-57 in the C-terminal helix and Arg-144 in the catalytic loop. The recently resolved structure of human IKK␤ suggests that in its active conformation, the activation loop phosphoserine 181 interacts with these cationic pocket residues, including lysine 171, to switch the kinase domain to a catalytically active conformation.…”
Section: Discussionmentioning
confidence: 99%
“…2, A and B) and active (Figs. 2, C and D) structures of this kinase based on the recently published structure of human IKK␤ (27) shows striking differences between the two states. In the active, phosphorylated IKK␤, the negatively charged phosphate moi- ety on serine 181 makes electrostatic interactions with cationic pocket residues Arg-57, Arg-144, and Lys-171, located, respectively, in the C-terminal helix, catalytic loop, and activation loop (Fig.…”
Section: Modeling Predicts the Mechanisms That Contribute To The Enhamentioning
confidence: 97%